2015
DOI: 10.1590/1807-1929/agriambi.v19n11p1086-1092
|View full text |Cite
|
Sign up to set email alerts
|

Condicionamento térmico primário de instalações rurais por meio de diferentes tipos de cobertura

Abstract: RESUMOObjetivou-se, com este trabalho, avaliar o conforto térmico proporcionado por diferentes tipos de cobertura, com base nas análises térmicas e nos índices de conforto térmico humano e zootécnico. A pesquisa foi realizada no período de 20 de março a 29 de maio de 2014, na UFRPE, no município de Recife, PE. Os tipos de cobertura analisados foram: telha de fibrocimento (Tfib), telha reciclada (Trec), telhado verde, grama, Zoysia japonica (Tgra) e telhado verde, amendoim, Arachis repens (Tame), com quatro rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…It emphasizes the occurrence of thermal delay for cooling in the prototypes due to the greater amount of mass inside, that is, prototypes and models maintains the same tendency of temperatures, as well as the sensitivity of the index in front of the others in the indication of thermal discomfort. Carneiro et al (2015) in the period from March/14 to May/14 obtained higher rates for BGHI in the conditions of predominant megathermic climate (As'), with average values of BGHI for the green roofs of 78. Cardoso et al (2011) evaluating the roofing conditions made with alternative materials (aluminized reciplac and Tetra Pak recycle) compared to clay roofing under hot conditions and with the use of similitude theory, it was generally observed that there was similarity between the results.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It emphasizes the occurrence of thermal delay for cooling in the prototypes due to the greater amount of mass inside, that is, prototypes and models maintains the same tendency of temperatures, as well as the sensitivity of the index in front of the others in the indication of thermal discomfort. Carneiro et al (2015) in the period from March/14 to May/14 obtained higher rates for BGHI in the conditions of predominant megathermic climate (As'), with average values of BGHI for the green roofs of 78. Cardoso et al (2011) evaluating the roofing conditions made with alternative materials (aluminized reciplac and Tetra Pak recycle) compared to clay roofing under hot conditions and with the use of similitude theory, it was generally observed that there was similarity between the results.…”
Section: Resultsmentioning
confidence: 96%
“…The importance of human and animal thermal comfort are shown on studies, among them those made by Carneiro et al (2015), Fagianelli et al (2014); Santos et al (2014); Tassi et al (2014); Jentzsch et al (2013), Melo et al (2013), and Passini et al (2013). By the exposed, the objective of this study was to evaluate the thermal comfort between prototypes in scale models and reduced size, using vegetation cover and expanded clay as an increase in thermal inertia, as well as to verify the similitude between the buildings in the indication of thermal comfort and air temperature indexes.…”
Section: Introductionmentioning
confidence: 99%
“…For buildings with wide space between walls and those using metallic structure in the roof, one option is the metallic tiles associated with polyurethane, insulating material (thermo acoustic tiles) or the use of PVC lining with interception, increasing the thermal insulation (ABNT, 2005a) . Another technological innovation is the use of green roofs which presents superior thermal performance compared to asbestos cement roof tiles and recycled roof tiles (Carneiro et al, 2015), because they reduce the heat flux in the roof (Latha et al, 2015), but the green roofs did not demonstrate complete effectiveness in Petrolina (Kolokotroni et al, 2016).…”
Section: Morningmentioning
confidence: 99%
“…In the last decades, new tools and techniques have been introduced in agriculture, being one of them the infrared thermography, which has been widely used to identify abnormalities in production systems (Carneiro et al, 2015). Thermography, together with the knowledge of material properties, local microclimate, and productivity indices, is useful information for the re-adaptation of materials used in trays for seedlings production.…”
Section: Introductionmentioning
confidence: 99%